Nanomaterial-induced pyroptosis: a cell type-specific perspective - Wang, Zhiyong; Wang, Min; Zeng, Xuan; Yue, Xupeng; Wei, Pei (Frontiers in Cell and Developmental Biology, 2024)
This review presents the advancements in nanomaterial (NM)-induced pyroptosis in specific types of cells. We elucidate the relevance of pyroptosis and delineate its mechanisms and classifications. We also retrospectively analyze pyroptosis induced by various NMs in a broad spectrum of non-tumorous cellular environments to highlight the multifunctionality of NMs in modulating cell death pathways. We identify key knowledge gaps in current research and propose potential areas for future exploration. This review emphasizes the need to focus on less-studied areas, including the pathways and mechanisms of NM-triggered pyroptosis in non-tumor-specific cell types, the interplay between biological and environmental factors, and the interactions between NMs and cells. This review aims to encourage further investigations into the complex interplay between NMs and pyroptosis, thereby providing a basis for developing safer and more effective nanomedical therapeutic applications.